América Latina Historia y Memoria ( Cahiers ALHIM ) cumple diez años - Nathalie Ludec (Nuevo mundo - Mundos Nuevos, 2017)
Amérique Latine histoire et mémoire. Les Cahiers ALHIM is devoted to the study of different themes of interest for Latin America: migrations, identities, education, religion, politics. Its historiographical contribution takes account of the memory-history binom. The first contributions of the journal deal with the theme of migrations. The journal is published by a research team « Amérique latine Histoire et Mémoire » from the Paris-VIII University. Responsable(s) : Perla Petrich and Nathalie Ludec ;